2017
DOI: 10.1111/mmi.13713
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular compartmentation, interdependency and dynamics of the cyclic AMP‐dependent PKA subunits during pathogenic differentiation in rice blast

Abstract: The cAMP-dependent PKA signalling plays a central role in growth, asexual development and pathogenesis in fungal pathogens. Here, we functionally characterised RPKA, the regulatory subunit of cAMP/PKA and studied the dynamics and organisation of the PKA subunits in the rice blast pathogen Magnaporthe oryzae. The RPKA subunit was essential for proper vegetative growth, asexual sporulation and surface hydrophobicity in M. oryzae. A spontaneous suppressor mutation, SMR19, that restored growth and conidiation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…A major challenge in deciphering the overall cAMP-PKA signaling is to fully understand the contribution(s) of both the catalytic subunits, CpkA and Cpk2, in M. oryzae . Previous studies revealed the importance of CPKA in appressorium formation and pathogenicity in M. oryzae ( Mitchell and Dean, 1995 ; Xu et al, 1997 ; Selvaraj et al, 2017 ). Our study provides a detailed elucidation of the function, dynamics and organization of the individual signaling components, CpkA and Cpk2 of the cAMP-PKA signaling in M. oryzae .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A major challenge in deciphering the overall cAMP-PKA signaling is to fully understand the contribution(s) of both the catalytic subunits, CpkA and Cpk2, in M. oryzae . Previous studies revealed the importance of CPKA in appressorium formation and pathogenicity in M. oryzae ( Mitchell and Dean, 1995 ; Xu et al, 1997 ; Selvaraj et al, 2017 ). Our study provides a detailed elucidation of the function, dynamics and organization of the individual signaling components, CpkA and Cpk2 of the cAMP-PKA signaling in M. oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…To get cpk AΔ cpk 2Δ, the cpk 2Δ construct was introduced into cpk AΔ strain. The CPK2 -GFP in pFGL820 (encoding sulfonyl urea resistance gene cassette) was constructed by sequential cloning of the eGFP ORF, the last 1kb and the downstream fragment of CPK2 ORF to yield the final construct pCPK2-GFP-Trpc construct ( Selvaraj et al, 2017 ). The GFP-CPK2 overexpression construct was created by fusing the Moh3 promoter with the cpk2 ORF, sequentially cloned in to pFGL1010G which encodes sulfonyl urea resistance with an ilV locus which facilitate ectopic single copy integration ( Yang and Naqvi, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations